1998
DOI: 10.1148/radiographics.18.2.9536484
|View full text |Cite
|
Sign up to set email alerts
|

CT characteristics of metastatic disease of the pancreas.

Abstract: Contrast material-enhanced computed tomographic (CT) scans obtained over a 1 0-year period in 66 patients with metastases to the pancreas were retrospectively reviewed. The primary tumors most commonly responsible for these metastases were renal cell carcinoma (30.3%) and bronchogenic carcinoma (22.7%). Metastases showed no predilection for any particular part of the pancreas. The majority

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
93
2
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(104 citation statements)
references
References 0 publications
2
93
2
7
Order By: Relevance
“…Therefore, the enhancement pattern of tumor tissue observed in all of our cases reflects a degree of vascular perfusion that is not typical of primary pancreatic adenocarcinoma. Several authors have also reported that rim enhancement is especially common in metastatic lesions larger than 1.5 cm in size, whereas smaller lesions tend to demonstrate homogeneous enhancement (9,12,13). In our study we did not observe a correlation between tumor size and pattern of enhancement.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…Therefore, the enhancement pattern of tumor tissue observed in all of our cases reflects a degree of vascular perfusion that is not typical of primary pancreatic adenocarcinoma. Several authors have also reported that rim enhancement is especially common in metastatic lesions larger than 1.5 cm in size, whereas smaller lesions tend to demonstrate homogeneous enhancement (9,12,13). In our study we did not observe a correlation between tumor size and pattern of enhancement.…”
Section: Discussioncontrasting
confidence: 77%
“…The tumors that metastasize most commonly to the pancreas are renal cell carcinoma, lung cancer, breast cancer and colorectal carcinoma followed by malignant melanoma and leiomyosarcoma (1,6). In most studies lung carcinomas or renal cell carcinomas are reported to be the most common (4,(8)(9)(10), although one study from Japan indicated stomach cancer as the main source suggesting population based differences (11). In our study, the most common primary malignancy was lung carcinoma (63.6%) followed by breast carcinoma (27.3%), but renal cell carcinoma did not comprise a significant percentage (9%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from Adsay et al (1) showed that pancreatic metastases, including those arising from lung cancer, RCC and digestive cancers, were predominantly of epithelial origin (65 of 81 cases). RCC metastasis to the pancreas has been extensively reported in the literature, and this is considered the most common origin of pancreatic metastatic lesions (18)(19)(20)(21)(22). A recent literature review (18), including 582 patients with pancreatic metastases, showed that the five most common primary tumors are RCC, lung carcinoma, colorectal cancer, melanoma, and breast carcinoma, representing 80% of all cases.…”
Section: Discussionmentioning
confidence: 99%